The Effect of Project Based Learning Model on Student Mathematics Learning Outcomes in the Covid-19 Pandemic Era - Yusrizal, Yusrizal; Pulungan, Syahrina Anisa (Budapest International Research and Critics University, 2021)
This research is motivated by the absence of an appropriate method to improve student learning outcomes during learning in the era of the covid-19 pandemic. The specific purpose of this research is to find out the differences in student learning outcomes in mathematics taught with project-based learning models compared to conventional learning models in learning in the era of the covid-19 pandemic. This research was conducted at SD Negeri 060931, Medan Amplas District. The population in the study were all students of SD Negeri 060931 with a total of 48 students consisting of 24 students in class V/a and 24 students in class V/b. The research instrument used a mathematics learning outcome test. The data analysis technique used an independent sample t test with a significant level of of 0.05. The results showed that the mathematics learning outcomes of students who were taught using the project based learning model were higher than those of students who were taught using the conventional learning model (Sig. 0.023 < 0.05; Mean Difference of 5.583).